The Effects of Rest Interval on Electromyographic Signal on Upper Limb Muscle during Contraction - Ahamed, Nizam Uddin; Rabbi, M. F.; Zahari, Taha; K., Sundaraj; Tasriva, Sikandar (Springer, 2017)
In this paper, the Electromyographic (EMG) signal was investigated on the Biceps Brachii muscle during dynamic contraction with two different rest intervals between trials. The EMG signal was recorded from 10 healthy right-arm-dominant young subjects during load lifting task with a standard 3-kg dumbbell for 10 seconds. Root mean square (RMS) has been used to identify the muscle function. The resting period was 2- and 5-minutes between each trial. The statistical analysis techniques included in the study were i) linear regression to examine the relationship between the EMG amplitude and the endurance time, ii) repeated measures ANOVA to assess differences among the different trials and iii) the coefficient of variation (CoV) to investigate the steadiness of the EMG activation. Results show that EMG signal is more active after 5 minutes rest period compare to 2-minutes gap. On the other hand, EMG signals were steady during 2-minutes rest (7.59%) compare to 5-minutes resting interval (16.14%). Results suggest that moderate interval between each trial is better to identify the muscle activity compare to a very short interval. The findings of this study can be used to improve the current understanding of the mechanics and muscle functions of the upper limb muscle of individuals during contraction which may prevent from muscle fatigue.